Phase 1/2 study of epacadostat in combination with ipilimumab in patients with unresectable or metastatic melanoma - Geoffrey T. Gibney; Omid Hamid; Jose Lutzky; Anthony J. Olszanski; Tara C. Mitchell; Thomas F. Gajewski; Bartosz Chmielowski; Brent A. Hanks; Yufan Zhao; Robert C. Newton; Janet Maleski; Lance Leopold; et al. (Journal for ImmunoTherapy of Cancer, 2019)
Abstract Background Epacadostat is a potent inhibitor of the immunosuppressive indoleamine 2,3-dioxygenase 1 (IDO1) enzyme. We present phase 1 results from a phase 1/2 clinical study of epacadostat in combination with ipilimumab, an anti-cytotoxic T-lymphocyte-associated protein 4 antibody, in advanced melanoma (NCT01604889). Methods Only the phase 1, open-label portion of the study was conducted, per the sponsor’s decision to terminate the study early based on the changing melanoma treatment landscape favoring exploration of programmed cell death protein 1 (PD-1)/PD-ligand 1 inhibitor-based combination strategies. Such decision was not related to the safety of epacadostat plus ipilimumab. Patients received oral epacadostat (25, 50, 100, or 300 mg twice daily [BID]; 75 mg daily [50 mg am, 25 mg pm]; or 50 mg BID intermittent [2 weeks on/1 week off]) plus intravenous ipilimumab 3 mg/kg every 3 weeks. Results Fifty patients received ≥1 dose of epacadostat. As of January 20, 2017, 2 patients completed treatment and 48 discontinued, primarily because of adverse events (AEs) and disease progression (n = 20 each). Dose-limiting toxicities occurred in 11 patients (n = 1 each with epacadostat 25 mg BID, 50 mg BID intermittent, 75 mg daily; n = 4 each with epacadostat 50 mg BID, 300 mg BID). The most common immune-related treatment-emergent AEs included rash (50%), alanine aminotransferase elevation (28%), pruritus (28%), aspartate aminotransferase elevation (24%), and hypothyroidism (10%). Among immunotherapy-naive patients (n = 39), the objective response rate was 26% by immune-related response criteria and 23% by Response Evaluation Criteria in Solid Tumors version 1.1. No objective response was seen in the 11 patients who received prior immunotherapy. Epacadostat exposure was dose proportional, with clinically significant IDO1 inhibition at doses ≥25 mg BID. Conclusions When combined with ipilimumab, epacadostat ≤50 mg BID demonstrated clinical and pharmacologic activity and was generally well tolerated in patients with advanced melanoma. Trial registration ClinicalTrials.gov identifier, NCT01604889. Registration date, May 9, 2012, retrospectively registered.